PENGARUH HARGA DISKON DAN PROMOSI TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA SALON NHABEAUTY DI JOMBOR BENDOSARI SUKOHARJO - Setyaningrum, Dian Ftriana; Purwanto, Edi; Triatmono, Agus (JURNAL ILMIAH EDUNOMIKA, 2024)
The research problem formulated in this study includes: Does the discount price have a significant effect on customer satisfaction at Nhabeauty Salon in Jombor Bendosari Sukoharjo? Does promotion have a significant effect on customer satisfaction at Nhabeauty Salon in Jombor Bendosari Sukoharjo? Does the discount price have a significant effect on customer loyalty at Nhabeauty Salon in Jombor Bendosari Sukoharjo? Does promotion have a significant effect on customer loyalty at Nhabeauty Salon in Jombor Bendosari Sukoharjo? Does customer satisfaction affect customer loyalty at Nhabeauty Salon in Jombor Bendosari Sukoharjo? Does the discount price significantly affect customer loyalty at Nhabeauty Salon in Jombor Bendosari Sukoharjo through customer satisfaction? Does promotion significantly affect customer loyalty at Nhabeauty Salon in Jombor Bendosari Sukoharjo through customer satisfaction? The first hypothesis suggests that the discount price affects customer satisfaction at Nhabeauty Salon in Jombor Sukoharjo as the t-value obtained is 0.026 < t-table 1.660, with a significance level (ρ) of 0.979 (not significant). The second hypothesis, which states that promotion affects customer satisfaction at Nhabeauty Salon in Jombor, is accepted since the t-value obtained is 6.185 with a significance level (ρ) of 0.000 (significant), as the t-value 6.185 > t-table 1.660. The third hypothesis, which states that discount prices affect customer loyalty at Nhabeauty Salon in Jombor Sukoharjo, is proven, with a t-value of 3.949 and a significance level (ρ) of 0.000 (significant). The fourth hypothesis, which states that promotion affects customer loyalty at Nhabeauty Salon in Jombor Sukoharjo, is also proven. This is because the t-value obtained is 6.185 with a significance level (ρ) of 0.000 (significant). The fifth hypothesis, which states that customer satisfaction affects customer loyalty at Nhabeauty Salon in Jombor Sukoharjo, is not proven, as the t-value obtained is 0.340 with a significance level (ρ) of 0.734 (not significant), and the t-value 0.340 < t-table 1.660. The sixth hypothesis, which states that discount prices do not affect customer loyalty through satisfaction, is not proven, as the t-value obtained is 0.025 with a significance level (ρ) of 0.980 (not significant). The seventh hypothesis, which states that promotion affects customer loyalty through satisfaction, is proven. This is because the t-value obtained is 1.787 with a significance level (ρ) of 0.070 (significant). Keywords: Discount Prices, Promotion, Customer Satisfaction, Customer Loyalty